The effect of patient characteristics to the acute procedural success and long term outcome of atrial tachycardia and atrial flutter cases undergoing catheter ablation - KEPEZ, ALPER (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: In the present study we aimed to demonstrate clinical characteristics, predictors of procedural success and long term recurrence of atrial tachyarrhythmia patients undergoing catheter ablation (CA). Patients and Methods: Consecutive patients who had undergone CA due to an atrial tachyarrhythmia in a single centre arrhythmia unit between 2012 - 2020 were screened. Predictors of procedural success and recurrence were analysed by logistic regression. Results: Study population consisted of 299 consecutive patients (95 [31.8 %] atrial tachycardia, 204 [68.2 %] atrial flutter cases);163 (54.5 %) were male; median age was 54 (IQR; 42-64). Median follow up was 330 (IQR; 90 - 810) days. Atrial flutter patients were older and had more co-morbidities. Acute procedural success rate was 82.1 % vs. 77.0 % (p= 0.313) and recurrence was 9.3 % vs. 21.6 % (p=0.022) in atrial tachycardia (AT) and atrial flutter (AFL) cases respectively. History of valvular or congenital heart disease surgery, left atrium diameter and age were found to be independent predictors of failed ablation, recurrence and post-procedural atrial fibrillation. Conclusion: Age, left atrium diameter, valvular or congenital heart disease surgery are independent predictors for acute procedural success, recurrence and post-procedural atrial fibrillation in AT and AFL patients who undergo catheter ablation.
Keywords: Atrial arrhythmia; Atrial tachycardia; Atrial flutter; Catheter ablation; RADIOFREQUENCY ABLATION; FIBRILLATION; PREDICTORS; RISK; ARRHYTHMIAS; FIBROSIS